2014
DOI: 10.1002/acs.2517
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the tuning constant in the Huber's function for robust modeling of piezoelectric systems

Abstract: This paper proposes a new modeling approach that is experimentally validated on piezoelectric systems in order to provide a black-box pseudolinear model for complex systems control. Most of the time, one uses physical based approaches. However, sometimes complex phenomena occur in the system due to atypical changes of the process behavior, output noise or some hard nonlinearities. Therefore, we adopt identification methods to achieve the modeling task. The microdisplacements of the piezoelectric systems genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Sometimes, complex phenomena are occurred in the system because of atypical changes of the process behavior, output noise, or some hard nonlinearities. This was confirmed by studying data for real phenomena [12][13][14][15]. Such cases are described by non-Gaussian distributions.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Sometimes, complex phenomena are occurred in the system because of atypical changes of the process behavior, output noise, or some hard nonlinearities. This was confirmed by studying data for real phenomena [12][13][14][15]. Such cases are described by non-Gaussian distributions.…”
mentioning
confidence: 56%
“…The block structure of pneumatic servo system is given in Figure 2. Moreover, many recent practical and theoretical studies have shown that in real systems, there are some observations that are inconsistent with the largest part of the population (outliers) [13][14][15]. Hence, the assumption that an exact distribution of stochastic disturbance e(k) is unknown will be used, but there is a priori information on the distribution class to which the disturbance belongs.…”
mentioning
confidence: 99%
“…Based on this theory, it is possible to get, in the statistical sense, robust recursive algorithms (reduced sensitivity to change of the disturbance distribution) for estimation of the parameters of dynamic phenomena. The application of the above mentioned ideas in the problems of identification and predictions was demonstrated in references [7][8][9][10][11][12][13]. Simulations have shown superiority of robust algorithms in relation to classical (linear) algorithms.…”
Section: Introductionmentioning
confidence: 99%